2015
DOI: 10.1111/nan.12295
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in extracellular matrix in Alzheimer's disease

Abstract: Present data support the hypothesis that significant ECM changes occur during the early stages of AD. ECM changes affecting brain microvascular functions could therefore drive disease progression and provide potential new early investigational biomarkers in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 77 publications
9
149
0
Order By: Relevance
“…Kalaria and Hedera (1995) have shown loss of staining of the endothelial markers CD31 and CD34 in capillaries but retained basement membrane COL4 immunoreactivity in AD brains. However, other studies have demonstrated no difference in CD31 staining between moderate-to-severe AD, subclinical AD, and control patients in frontal and temporal cortices (Lepelletier et al, 2017). Zhang et al (1998) found no difference in endothelial markers in brains with severe arterial and arteriolar CAA, with or without AD, compared with controls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kalaria and Hedera (1995) have shown loss of staining of the endothelial markers CD31 and CD34 in capillaries but retained basement membrane COL4 immunoreactivity in AD brains. However, other studies have demonstrated no difference in CD31 staining between moderate-to-severe AD, subclinical AD, and control patients in frontal and temporal cortices (Lepelletier et al, 2017). Zhang et al (1998) found no difference in endothelial markers in brains with severe arterial and arteriolar CAA, with or without AD, compared with controls.…”
Section: Discussionmentioning
confidence: 97%
“…Thickening of the capillary basement membrane with increase in collagen content, which could disrupt transport into and out of the brain, has also been reported in the brains of subjects with AD and Parkinson disease (Farkas et al, 2000; Kalaria and Pax, 1995; Tian et al, 2006). Furthermore, these vascular changes appear to occur early in the course of disease as COL4, perlecan, and fibronectin, components of the perivascular extracellular matrix, were increased in both subclinical AD subjects and AD patients compared with controls, without a further increase in AD patients compared with those with subclinical AD (Lepelletier et al, 2017). However, other studies have shown no difference in the collagen content in the cerebral vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, fibronectin triggers the activation of microglia in vitro (33), and thus may stimulate macrophage/microglial activation in RIBI. Fibronectin is also increased in the cortex (34) and plasma (35) of humans with clinical and subclinical Alzheimer’s disease. The cortical deposition of fibronectin may play a role in the pathology of cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations to extracellular matrix (ECM) stiffness and density occur during tissue aging [1] and disease [25] and have the potential to impact cell behavior within the tissue. For example, numerous in vitro studies have shown that substrate rigidity can influence the organization and generation of intracellular forces [6], overall cell morphology [7, 8], and intracellular signaling [9, 10], thereby affecting the differentiation of stem cells [11], migration of a variety of cell types [1214], and invasiveness of cancer cells [15].…”
Section: Introductionmentioning
confidence: 99%